2004
DOI: 10.1088/0953-2048/18/1/013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of B2O3 addition on the properties of melt-processed YBa2Cu3O7−δ

Abstract: Samples of YBa2Cu3O7−δ, having about 30% Y2BaCuO5, were prepared with a melt-process method by adding B2O3 up to 0.5 wt% to the oxides. The structural and superconducting properties of the samples were studied by x-ray diffraction, x-ray fluorescence, scanning electron microscope, magnetization and magneto-optic techniques. B2O3 additions during the melt-processing enlarge intergrain regions that weaken the conduction links between the grains. Tc drops by 1.0–6.0 K, and at 50 K Jc decreases from about 1.6 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…4; Rn is the normal-state value of the surface resistance obtained from Eq. This finding is ascribable to an increase of the effective penetration depth, which in granular samples is ruled by the intergrain field penetration depth, and is consistent with the observation that part of B atoms resides at the grain boundaries reducing the intergrain Josephson current [21].…”
Section: Surface Resistance At Zero Magnetic Fieldsupporting
confidence: 89%
See 3 more Smart Citations
“…4; Rn is the normal-state value of the surface resistance obtained from Eq. This finding is ascribable to an increase of the effective penetration depth, which in granular samples is ruled by the intergrain field penetration depth, and is consistent with the observation that part of B atoms resides at the grain boundaries reducing the intergrain Josephson current [21].…”
Section: Surface Resistance At Zero Magnetic Fieldsupporting
confidence: 89%
“…This finding has been ascribed to a reduction of the charge carries due to an increase of the defect density. On the other hand, several authors [14,21,22,23] have suggested that dopants as Li and B can substitute Cu atoms in the Cu-O chains, breaking their continuity and, consequently, reducing their ability to transfer holes to the superconducting CuO 2 planes. So, the ρ increase associated to the H c2 decrease, we obtained in Y-12, may be due to the defect-induced reduction of carrier density.…”
Section: Field-induced Variation Of Rsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, B 2 O 3 addition during Bi Pb 2 Sr 2 Ca 2 Cu 3 O 10 (Bi-2223) synthesis was shown to promote the growth of the high-phase by inducing more partially melted liquid phase of the Bi-based superconductors. These additions up to 0.01 wt % are reported to increase the critical current density c of Bi-2223 ceramics and silver-sheathed tapes [5]. Studies of boron effects on the YBaCuO system are very limited.…”
mentioning
confidence: 99%